Analisis SWOT Produk Kreatif Evia Abon Cabe di Parung Panjang Bogor - Laelatul Azkiyah; Dedi Junaedi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2021)
The purpose of this service is to observe and identify the strengths/weaknesses of internal and external factors of Abon Cabe Evia's business in Parung Panjang, Bogor. The method used is qualitative descriptive analysis. The results are: Internal factors that become the main strength of Abon Cabe Evia is that the production does not use flavoring ingredients or monosodium glutamate so that the product has natural ingredients, while the weakness is that marketing through online and offline media is not optimal. External factors that become opportunities are market trends and consumption that continues to increase so that the potential to get more customers is potential, while the threat is the emergence of competitors which causes intense business competition.